POST-SECONDARY REGIONAL ACCREDITATION ASSESSMENT STANDARDS IN THE UNITED STATES - Cumming, Tammie; Zhao, Yongchao (European Scientific Journal, ESJ, 2015)
Regional accreditation organizations in the United States have increased their demands for transparency of student outcomes, as well as articulated the demands for a continuous improvement model that includes the assessment and evaluation of student learning. A review of the regional accreditation organizations in the United States was conducted to determine the assessment methods required to meet the accreditation standards. Two broad categories of assessment methods were identified as direct and indirect methods; however, a universal definition of the two assessment methods did not exist. This review resulted in the categorization of both methods as a resource for those responsible for assessment activities.